Atypical presentation of acute myeloid leukemia with jugular venous thrombosis and multifocal osteomyelitis - Debarati Das; Maaz Ahmed; G V Basavaraj; K S Sanjay (Wolters Kluwer Medknow Publications, 2019)
The patients with leukemia have a high risk of venous thromboembolism and rarely, multiple bone sites can be involved to present as multifocal osteomyelitis. A four year old child had cellulitis, multifocal osteomyelitis, left pneumonia with pleural effusion, cervical lymphadenopathy, hepatomegaly and left internal jugular vein thrombosis, finally diagnosed as acute myeloid leukemia. A timely bone marrow biopsy study should be considered in a child with deep vein thrombosis along with multifocal osteomyelitis to diagnose and intervene acute myeloid leukemia early.